2015
DOI: 10.1002/hyp.10443
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of hydroclimatological trends and variability in the Lake Naivasha basin, Kenya

Abstract: Recent hydro‐climatological trends and variability characteristics were investigated for the Lake Naivasha basin with the aim of understanding the changes in water balance components and their evolution over the past 50 years. Using a Bayesian change point analysis and modified Mann–Kendall tests, time series of annual mean, maximum, minimum, and seasonal precipitation and flow, as well as annual mean lake volumes, were analysed for the period 1960–2010 to uncover possible abrupt shifts and gradual trends. Dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The negative trends tended to be in the westernmost sectors. During this same period a reduction in lake levels and river flow in the Lake Naivasha Basin occurred, but commensurate trends in rainfall could not be found [Odongo et al, 2015]. Studies of rainfall in northern Ethiopia [Conway et al, 2004;Kiros et al, 2016] found trends in northern Ethiopia to be generally insignificant and spatially diverse.…”
Section: Recent Trendsmentioning
confidence: 89%
“…The negative trends tended to be in the westernmost sectors. During this same period a reduction in lake levels and river flow in the Lake Naivasha Basin occurred, but commensurate trends in rainfall could not be found [Odongo et al, 2015]. Studies of rainfall in northern Ethiopia [Conway et al, 2004;Kiros et al, 2016] found trends in northern Ethiopia to be generally insignificant and spatially diverse.…”
Section: Recent Trendsmentioning
confidence: 89%
“…Results show a globally homogeneous situation with nevertheless abrupt changes as well as in precipitations than in flows. In addition to this, a net diminishing of about 9.35 × 10 6 m 3 per year of the volume has been noticed [6]. It has been proven that changes in rainfall characteristics are one of the most relevant signs showing current climate alterations [31].…”
Section: Introductionmentioning
confidence: 97%
“…Many scientific studies in hydroclimatic field are oriented towards determining the states, the causes and consequences of climate variability and change [2] [3]. According to these studies, climate change is due to increased greenhouse gas concentrations, while trend and shift in runoff time series data are consequence of climate change effects, land use change (urbanization, clearing, deforestation and others) or change in management practice [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many applications have been found in climate change studies all over the world (e.g. Adamowski and Bougadis, 2003;Burn and Amir, 2013;Chowdhury and Beecham, 2010;Crisci et al, 2002;Dogan, 2015;Dumanski et al, 2015;Odongo et al, 2015) and in China (e.g. Zhang et al, 2014;Zhao et al, 2008).…”
Section: Methodsmentioning
confidence: 99%